2010
DOI: 10.1037/a0018709
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy, professional relationships, and ethical considerations in the myspace generation.

Abstract: The pervasive use of Internet technologies has created new ethical dilemmas for psychology trainees and professionals. In particular, Web sites that allow users to post personal information have sparked controversy regarding the amount of freedom psychologists should have in placing personal information online and how discovering such information may impact professional relationships, including the therapeutic relationship. Results from a graduate student survey (N ϭ 302) address the prevalence of the use of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(139 citation statements)
references
References 16 publications
(18 reference statements)
4
133
1
1
Order By: Relevance
“…This is a similar number to findings by Lehavot et al (2010), who reported 27% of graduate students had "Googled" clients. Interestingly, a recent study by DiLillo and Gale (2011) reported that almost their entire satnple of graduate students (97.8%) reported searching for at least one client's information in the past year.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is a similar number to findings by Lehavot et al (2010), who reported 27% of graduate students had "Googled" clients. Interestingly, a recent study by DiLillo and Gale (2011) reported that almost their entire satnple of graduate students (97.8%) reported searching for at least one client's information in the past year.…”
Section: Discussionsupporting
confidence: 90%
“…A few empirical studies have investigated both graduate students' and psychologists' online experience and attitudes (DiLillo & Gale, 2011;Lehavot et al, 2010;Tunick, Mednick & Conroy, 2011). In general, results indicated that psychologists and trainees are experiencing these online interactions with some regularity.…”
Section: Ethicsmentioning
confidence: 95%
“…Fox (2009) found that 61% of American adults report looking online for health information, and Lehavot et al (2010) found that 7% of student psychotherapists reported that a client disclosed that he or she obtained online information about them.…”
Section: Preventing and Managing Boundary Violations Onlinementioning
confidence: 97%
“…), among others (Bamett & Scheetz, 2003;Koocher & Keith-Spiegel, 1998;Lehavot, Bamett, & Powers, 2010).…”
mentioning
confidence: 96%